Hodgkin lymphoma transformation of chronic lymphocytic leukemia—A real life data from the Polish Lymphoma Research Group. Issue 4 (14th June 2019) - Drozd‐Sokołowska, Joanna; Zaucha, Jan Maciej; Żółtak, Tomasz; Jamroziak, Krzysztof; Grzybowska‐Izydorczyk, Olga; Witkowska, Magdalena; Waszczuk‐Gajda, Anna; Kaźmierczak, Maciej; Szczepaniak, Andrzej; Subocz, Edyta; Knopińska‐Posłuszny, Wanda; Hołojda, Jadwiga; et al.
Abstract: Richter transformation (RT) of chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) to Hodgkin lymphoma (HL) is a rare and unexpected event in the course of the disease and data on this phenomenon is still limited. To better understand the clinical and histological characteristics and the outcomes of HL variant of RT (HvRS) the Polish Lymphoma Research Group performed a nationwide survey which identified 22 patients with histologically proven HvRS diagnosed between 2002 and 2016. There were 16 (73%) males. The median age at CLL/SLL and HvRS diagnosis was 59 (39‐77) and 64 (40‐77) years, respectively. The median interval between CLL/SLL and HvRS diagnosis was 38 months (range: 0‐187). All patients had an advanced stage HL, and majority, 17 (77%), presented with B symptoms. The predominant subtypes of HL were nodular sclerosis (12; 55%) and mixed cellularity (9; 41%). Eighteen patients received non‐palliative treatment, including 13 who received driamycin, bleomycin, vinblastine, and dacarbazine (ABVD) regimen first line. Objective response was: 50%, with 33% complete remissions (61% and 46% for ABVD, respectively). Median overall survival reached 13.3 months (95% CI, 3.7‐NA). The only adverse prognostic factor for survival was a higher number (≤1 versus ≥2) of prior lines of treatment given for CLL/SLL with HR 3.57 (95% CI, 1.16‐10.92). We conclude, HvRS harbors a poor prognosis, especially in patients heavily pretreated for CLL/SLL. Response to standard first‐line anti‐HL chemotherapy is unsatisfactory, and new agents should be tested to improve the outcome.